The relationship between online learning self-efficacy, informal digital learning of English, and student engagement in online classes: the mediating role of social presence - Wu, Ronglan (Frontiers in Psychology, 2023)
Introduction This study investigates the interplay between Online Learning Self-Efficacy (OLSE), Informal Digital Learning of English (IDLE), student engagement in online classes, and the mediating effect of Social Presence (SP) among intermediate Chinese English as a Foreign Language (EFL) students. The research sample consisted of 389 participants enrolled in online English courses within a chain of language schools. Methods Data collection involved the use of validated scales to assess OLSE, IDLE, SP, and online student engagement. Structural Equation Modeling (SEM) was employed for data analysis. Results The findings revealed direct influences of OLSE and SP on online student engagement. Additionally, IDLE exhibited a positive impact on online student engagement, with a partial mediation effect through SP. This suggests that informal digital English learning significantly contributes to students’ engagement in online classes, with this influence being facilitated by the sense of social presence experienced by students during virtual interactions. Discussion This research underscores the importance of OLSE, IDLE, and SP in shaping student engagement within online learning environments. The results highlight that fostering informal digital English learning can enhance students’ active participation in online courses, with SP serving as a key mediator in this relationship. These insights provide valuable guidance for educators and institutions seeking to improve student engagement in online educational settings.